Evapotranspiração e produção da abóbora cultivar bárbaba sob diferentes níveis de salinidade e de adubação nitrogenada - Lima, Rozana Maria de Sousa (Universidade Federal Rural do Semi-Árido, 2013)
The increased demand for water for irrigation has led farmers to use water with higher salinity, and its use is subject to the crop tolerance to salinity and irrigation management . The nitrogen has provided a significant increase in production saline environment and reduces the effect of the salts . This work aimed to study the effects of different levels of salinity of irrigation water and nitrogen applied through fertigation in evapotranspiration and yield of pumpkin, the climatic conditions of the region of Mossoró - RN. An experiment in field conditions at the Experimental Farm UFERSA, Mossoró, RN was developed. The treatments consisted of irrigation application with five salinity levels (S1 = 0.5, S2 = 1.5, S3 = 2.5, S4 = S5 = 3.5 and 4.5 dS m- 1) and three Nitrogen doses ( 30 , 100 , 170 % of the recommended dose) . To estimate the ETo Penman - Monteith equation parameterized by FAO was used. The meteorological data required for estimating ETo were collected by an automatic weather station, installed in the experimental area. The ETc was measured by four weighing lysimeters installed in salinity levels S1 and S5. The nutritional status of plants was evaluated by foliar analysis of the flowering period. Periodic reviews of the evolution of soil salinity were performed using soil samples throughout the crop cycle. The results showed that ECT decreased between the irrigation water S1 and S5, where during the entire evaporation cycle was 300.29 and 279.20 mm, respectively. As for the mean values Kc's the phenological stages I, II, III, IV, 0.42 , 0.68 , 1.08, 0.78 for the S1 treatment and 0.41 , 0.62 , 0.92, 0.60 for the S5 treatment , showing that the obtained for Kc's were always higher than those obtained for Kc's S5 level S1 level . There was a significant effect of nitrogen on the yield components, except for the average mass of total and marketable fruit. The total and marketable yield of fruits were significantly affected by the quality of the irrigation water and by nitrogen rates
Evapotranspiration and production pumpkin growing Bárbaba under different levels of salinity and nitrogen
Keywords: Squash; Barbara; Salinization; Nitrogen; Abóbora; Bárbara; Salinização; Nitrogênio; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA::ENGENHARIA DE SOLO E AGUA::IRRIGACAO E DRENAGEM